Assessment of Cardiovascular Risk and Obesity - Batajoo, Kabita Hada; Shrestha, Roshana; Sharma, Madhusudan (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: There are numbers of epidemiological studies that shows clear correlation between obesity and cardiovascular risk factors like systemic hypertension, diabetes, dyslipidemia. The primary aim of this study was to assess the absolute cardiovascular risk (ACR) and cardiovascular risk factors in obese patient.Methods: A descriptive cross sectional study was conducted at this hospital in a population who came for preventive health checkup package. The study was done over a period of 2 years from April 2011 to march 2013. Hypertension was defined as per JNC-7 guidelines. Lipid profile was assess following the criteria of Third report of National Cholesterol Education. Cardiovascular risk assessment was done by Farmingham risk assessment calculator 2008.Result: Total 197 people: male 95(55.5%), female 75(44.5%) participated in this study. Out of which 101 (59.4%) had high BMI with equal prevalence among gender. There was significant relation of BMI with high cholesterol and high triglyceride with p- 0.021 and p-0.004 respectively. However there was no statistically significant relation with alcohol use, smoking, hypertension and diabetes .The study also revealed that 22% of population had moderate and 18% had high ACR but correlation between ACR and BMI was not significant statistically (p=0.091). .However in routine ultrasound finding there was strong association of fattyliver with high BMI 59% in overweight and in 22% obese which was statistically significant P<0.001Conclusion: Prevalence of population with BMI above normal was high in this study though it did not show any clear relationship with ACR. However this study has formulated an important hypothesis that high cholesterol can be the only indicator that gives the clue towards cardiovascular risk.